The Hemodynamic Performance of the Perceval Sutureless Aortic Valve in a Propensity-Matched Comparison to the Carpentier–Edwards Perimount and Perimount Magna Ease Valves for Aortic Valve Replacement - Kueri, Sami; Berger, Tim; Puiu, Paul-Cătălin; Alhamami, Yasir; Diab, Nawras; Czerny, Martin; Hochholzer, Willibald; Siepe, Matthias (The Thoracic and Cardiovascular Surgeon, 2022)
Objectives The Perceval valve was shown to facilitate minimal-invasive operations and shorten operative times. We aimed to compare the early results of the Perceval valve to those of well-established valves, namely the Carpentier–Edwards Perimount and Perimount Magna Ease valve protheses, in terms of their clinical and hemodynamic performances.Methods This is a single-center, retrospective, observational cohort study. For every patient operated with a Perceval valve, the last patient before and the next following patient receiving a Perimount valve was included in a control group leading to a 2:1 ratio (Perimount:Perceval). A propensity score matching was used and a subgroup analysis was performed to compare early and late Perceval patients as the sizing technique was changed over time.Results From November 2013 to November 2017, 423 patients were identified. These included 141 consecutive patients receiving a Perceval valve through a full- or a hemi-sternotomy. In addition, 282 patients receiving a Perimount or a Magna Ease valve were enrolled. After propensity score matching, 127 matched patients were compared. Operating times were shorter and postoperative transvalvular pressure gradients were lower in the Perceval group (15 vs. 17 mmHg, p = 0.002). There was no difference in mortality and stroke rates. The incidence of new pacemaker implantations was higher in the Perceval group (7.1 vs. 18.9%, p = 0.005), mainly due to a very high incidence in the early phase of our Perceval experience prior to a change in the Perceval implantation technique. Subgroup analysis showed significantly better results in the late Perceval group.Conclusion Surgical outcome was good in both groups. The Perceval valve exhibited lower postoperative gradients, and the need for pacemaker implantation was higher and can be reduced by avoiding oversizing.
Keywords: sutureless Perceval valve; Perimount valve; aortic valve replacement; mean gradient